Combinational Drug Therapy and Electrolyte Disorder in a Hypertensive Patient–A Case Report - Mandava, Poojitha; Kiranmai, Tunuguntla Kusuma Naga Venkata Raja; Mounika, Pilli Sai; Babu, A.M.S Sudhakar (Indian Journal of Pharmacy Practice)
Hyponatremia and Hypokalemia are Electrolyte Disorders which are less common but serious effects that lead to severe complications such as death. This usually occurs due to imbalance between water and electrolytes in body often presented with signs and symptoms of Vomiting, Diarrhea, and Generalised Weakness. The common causes include decreased intake, increased excretion of Sodium, Potassium and rarely Drug induced. Immediate correction of electrolytes is very crucial by stopping the causative agents and providing additional support. This is a Case Report presenting: A 72 year old male patient presented to the hospital with symptoms of Generalised weakness and with past history of hypertension and Diabetes and he is on regular medication. Laboratory investigations showed abnormal values of Serum & Urinary Sodium and Potassium ions. On observing this case, it is found that it is the effect of ARB+Thiazide drug therapy and is managed by treating with additional supplements of Sodium [0.9% Normal Saline] & Potassium [Syrup Potassium Chloride] together with alteration of ARB+Thiazide therapy with “Loop Diuretics + Potassium Sparing Diuretics”, which showed Good Results both by Physical response and Laboratory values.
Keywords: Hyponatremia; Hypokalemia; ARB's; Thiazide drugs; Combinational Drug Therapy; Drug Induced Electrolyte Disorder